Changes in mediators of pro‐cell growth, senescence, and inflammation during murine gestation. (12th January 2020) - Lavu, Narmada; Sheller‐Miller, Samantha; Kechichian, Talar; Cayenne, Samir; Bonney, Elizabeth A.; Menon, Ramkumar
Abstract: Problem: Senescence of the fetal membranes and senescence‐associated inflammation have been associated with parturition at term and pre‐term in both mice and humans. Using a pregnant mouse model, we determined changes in multiple molecular signalers contributing to senescence and inflammation associated with parturition. Method of study: Fetal membranes were collected from timed‐pregnant CD‐1 mice on gestation days (E) 13, 15, 17, 18, and 19. Immunohistochemistry (IHC) localized pro‐cell growth factors glycogen synthase kinase 3β (GSK3β) and β‐catenin. Gestational age‐associated changes in pro‐cell growth vs senescence mediators (p38 mitogen‐activated protein kinase [p38MAPK]), prooxidants (heme oxygenase‐1 [HO‐1], peroxisome proliferator‐activated receptor γ [PPARγ]), and pro‐ and anti‐inflammatory cytokines (IL‐6, IL‐8, IL‐10, and IL‐1β) were determined by Western blots and Luminex assays. Results: Fetal membrane expressions of phosphorylated forms of GSK3β (inactivation) and p38MAPK (activation) increased, while β‐catenin expression decreased, as gestation progressed. Antioxidant HO‐1 expression decreased while PPARγ increased toward term gestation. IL‐6 and IL‐8 concentrations were highest on E19 (day of delivery), while IL‐10 and IL‐1β concentrations were highest on E15. Conclusion: Mouse fetal membranes showed a progressive senescence marker increase coincided with downregulation of cell growth factors. Development of senescence is associated with inflammation. Senescence‐associated changes are natural and physiologic and indicative of fetal membranes' readiness for parturition.